Experimental Salmonella enterica serovar Pullorum infection in two commercial varieties of laying hens - Pinheiro, Lucas Augusto Soeiro [UNESP]; De Oliveira, Gláucia Helaine [UNESP]; Berchieri Jr., Angelo [UNESP] (Taylor & Francis, 2001)
An experiment was carried out to investigate the biology of Salmonella Pullorum in two varieties of laying hens, from 5 days of age up to 9 months. One variety was resistant to systemic salmonellosis (light layers producing white eggs) and the other was considered susceptible (brown layers producing brown eggs). The brown birds were more affected by the infection, showing signs of clinical disease in the first month of life. Later, these signs disappeared, but postmortem examination revealed persistent gross pathological changes in the liver, spleen, heart and ovary. The rapid agglutination test detected reactors throughout the experiment, with the strongest agglutination from 1 to 7 months post-infection. S. Pullorum was isolated from some of the organs and the eggs laid throughout the experiment. The relationship between white birds and S. Pullorum was less intense, and there were no noticeable signs of disease. There were few gross pathological changes, and the bacteria were isolated infrequently and only for a brief period after infection, although contaminated eggs were laid by these birds. The strongest serological response in the white chickens occurred between the second and the fifth month post-infection.